2017
DOI: 10.3390/en10111741
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Additives on the Dehydrogenation of Amorphous Manganese Borohydride and Its Crystalline Form after Solvent Filtration/Extraction

Abstract: Abstract:A non-stoichiometric, amorphous a-Mn(BH 4 ) (2x) hydride, accompanied by a NaCl-type salt, was mechanochemically synthesized from the additive-free mixture of (2NaBH 4 + MnCl 2 ), as well as from the mixtures containing the additives of ultrafine filamentary carbonyl nickel (Ni), graphene, and LiNH 2 . It is shown that both graphene and LiNH 2 suppressed the release of B 2 H 6 during thermal gas desorption, with the LiNH 2 additive being the most effective suppressor of B 2 H 6 . During solvent filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Alternatively, Desrosiers et al [29] reported that at low gas exposures and heating to 500 K resulted in complete decomposition of B2H6, leaving B bonded to the Ni(100) surface. More recently, we proposed that LiNH2 reacts with B2H6 in an exothermic reaction during desorption, resulting in the formation of either lithium hydride or lithium borohydride accompanied by boron nitride [30].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Alternatively, Desrosiers et al [29] reported that at low gas exposures and heating to 500 K resulted in complete decomposition of B2H6, leaving B bonded to the Ni(100) surface. More recently, we proposed that LiNH2 reacts with B2H6 in an exothermic reaction during desorption, resulting in the formation of either lithium hydride or lithium borohydride accompanied by boron nitride [30].…”
Section: A C C E P T E Dmentioning
confidence: 99%